3D printed triply periodic minimal surfaces as advanced structured packings for solvent-based CO2 capture. Issue 4 (17th March 2023) - Ellebracht, Nathan C.; Roy, Pratanu; Moore, Thomas; Gongora, Aldair E.; Oyarzun, Diego I.; Stolaroff, Joshuah K.; Nguyen, Du T.
Abstract : Advanced structured packing geometries fabricated with 3D printing were used for absorber CO2 capture with a liquid solvent. Compared to conventional packing, they had greatly enhanced (90–140%) effective surface areas and comparable hydrodynamics. Abstract : Point-source CO2 capture is a critical technology for industrial decarbonization and certain CO2 removal processes. Solvent-based CO2 absorption is a mature process, but the capital investment and energy requirements are substantial, especially when economic drivers for its deployment are tenuous. We utilized additive manufacturing and computational fluid dynamics to screen and prototype structured packings in the vast design space accessible via advanced manufacturing and computer-aided design. 3D-printed triply periodic minimal surfaces (TPMS) were tested as advanced packing geometries for CO2 capture from simulated flue gas (10% CO2 ) and evaluated alongside a representative industrial packing geometry, Mellapak 250Y. 1D model fits of experimental absorption data revealed 49–61% increases in mass transfer performance ( k L a eff ) and 91–140% increases in effective gas–liquid interfacial area in TPMS packings (Gyroid and Schwarz-D) compared to 250Y. These advanced structured packings also featured similar or better maximum fluid loads and pressure drops than 250Y, reinforcing their industrial potential. Together with the capability to natively distribute fluid shown by the TPMS geometries, the performance improvements realized could reduce absorber capital costs by more than 30%.